Determination of Antioxidant Property of Brown Alga Colpomenia sinuosa - Vijayabaskar, P.; Lekameera, R.; Somasundaram, S. T. (Current Topics in Agricultural Sciences Vol. 6, 2022)
In vitro study is a simple, calorimetric qualitative method, which could mimic the in vivo system and would help to validate the antioxidant potential of a Seaweed methanol extracts. Colpomenia sinuosa, a brown alga, was tested for antioxidant properties using DPPH (1,1-diphenyl-2-picryl hydrazyl), nitric oxide radical, hydrogen peroxide, ABTS radical scavenging, and Total antioxidant capacity (TAC) inhibitory assays. The dimethyl sulphoxide (DMSO) and methanol extracts showed highest antioxidant activity in DPPH (96.56 and 88.57%), nitric oxide radical (81.2 ± 4.1% and 76.69 ± 3.1 %), hydrogen peroxide (70.7 ± 3.5 and 56.6 ± 2.0%) and ABTS (76.8 ± 3.8% and 74.0 ± 2.8%). The total antioxidant capacity (60.3 ± 4.3 and 57.0 ± 2.0) test revealed modest activity. The activity was greater and comparable to that of commercial antioxidants butylated hydroxy anisole (BHA) (87.38 ± 1.32%) and butylated hydroxy tolune (BHT) (56.05 ± 0.19%) at 2 mg/ml concentration. C. sinuosa's strong free radical scavenging activity suggested that it would be a good source of natural antioxidant lead compounds.